Pony confidential eaudiobook - Lynch, Christina (Books on Tape, 2024)
An NPR "Book of the Day" In this one-of-a-kind mystery with heart and humor, a hilariously grumpy pony must save the only human he’s ever loved after discovering she stands accused of a murder he knows she didn’t commit. Pony has been passed from owner to owner for longer than he can remember. Fed up, he busts out and goes on a cross-country mission to reunite with Penny, the little girl whom he was separated from and hasn’t seen in years. Penny, now an adult, is living an ordinary life when she gets a knock on her door and finds herself in handcuffs, accused of murder and whisked back to the place she grew up. Her only comfort when the past comes back to haunt her is the memory of her precious, rebellious pony. Hearing of Penny’s fate, Pony knows that Penny is no murderer. So, as smart and devious as he is cute, the pony must use his hard-won knowledge of human weakness and cruelty to try to clear Penny’s name and find the real killer. This acutely observant, feel-good mystery reveals the humanity of animals and beastliness of humans in a rollicking escapade of epic proportions.